A critique of the official report on the evacuation of the World Trade Center: continued doubts. Issue 4 (6th September 2013) - Hotchkiss, H. Lawrence; Aguirre, B.E.; Best, Eric
Abstract : This paper criticises the conclusions and the unanswered questions in the National Institute of Standards and Technology (NIST)'s official report on the evacuation of the World Trade Center in New York City, United States, on 11 September 2001. It reviews the extent to which the report disregards several conventional statistical methods and comments on the NIST's refusal to share the machine‐readable data file with the scientific community for replication and further analysis. Problems lie in the sampling methods employed, the treatment of missing data, the use of ordinary least squares (OLS) with binary dependent variables, the failure to document the scalability of the scales used, the lack of tests to check for constant error variance, and the absence of overall fit tests of the model. There are also conceptual and theoretical issues, such as the absence in the report of considerations of the influence of group‐level processes and their impact on the collective behaviour of evacuating collectivities.